Perancangan Sistem Informasi Layanan E-Consultation Anggota Jemaat GMAHK Ke Pendeta Berbasis Web menggunakan Laravel dan Vue.Js - Simbolon, Yonatan; Pakpahan, Andrew (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2024)
In the digital era, access to spiritual services has become a challenge for church members living in remote areas or those with limited time. This study is driven by the need of the Seventh-day Adventist Church (GMAHK) to provide an efficient online consultation platform between church members and pastors. This research developed a web-based e-consultation application using the Laravel and Vue.js frameworks. The development method used is the Rational Unified Process (RUP), an iterative and incremental software development model. This process consists of four main phases: Inception (user needs analysis), Elaboration (system architecture design), Construction (system development and testing), and Transition (implementation and system refinement based on user feedback). The main features include consultation scheduling, visitation requests, and direct interaction through live chat. This e-consultation application offers a practical and effective solution for flexible spiritual consultation services that can be accessed without geographical barriers.